Influence of genotypes and inoculation method on production of lentil (Lens culinaris) under dryland temperate conditions of Kashmir valley - Singh, Ummed; Saad, A A; Singh, S R; Kamaluddin, Kammaluddin (The Indian Journal of Agricultural Sciences, 2008)
A field experiment was conducted during winter (rabi) seasons of 2005-06 and 2006-07 at Regional Research Station of the University, Wadura, Sopore (Jammu & Kashmir) to find out the relative performance of 3 genotypes (’SKL 9’, ’SKL 16’ and ’Shalimar Masoor 1’) and inoculation methods on growth, yield. N and P uptake and nodulation of lentil (Lens culinaris Medik). The mean performance indicated significant superiority of ’Shalimar Masoor 1’ to ’SKL 16’ and ’SKL 9’ in terms of growth, yield attributes, grain yield (0.81,0.72 and 0.64 tonnes/ha), N and P uptake and nodulation and also recorded marked reduction in days (5.9 days) to flowering and maturity. Rhizobium inoculation with seed and soil inoculation methods significantly improved the growth, yield attributes, grain yield, straw yield, nodulation and N and P uptake in lentil. Pseudomonas alone either seed inoculated or soil inoculated recorded markedly more number and dry weight of nodules at all the intervals and growth and yield attributes and yield over uninoculated control. Seed inoculation with Pseudomonas markedly enhanced dry matter production (142.6 g/m row), grains/pod (1.49), grain weight/plant (1.45 g), grain yield (0.72 tonnes/ha), straw yield, N and P uptake and nodulation at all the intervals over soil inoculation with Pseudomonas as at par in terms of days to flowering and maturity and pods/plant. Dual inoculation of Rhizobium+Pseudomonas with both the methods recorded significantly higher number and dry weight of nodules, N and P uptake, yield, yield attributes and growth parameters over individual inoculation with Rhizobium and Pseudomonas with respective methods. Dual inoculation of seed with Rhizobium+Pseudomonas markedly gave 21.2 and 48.9% higher grain yield and 28.5 and 55.9% more straw yield over the dual inoculation of soil with Rhizobium+Pseudomonas and uninoculated control respectively. Seed inoculation method gave more occupancy in nodules than soil inoculation with all the treatments. Dual inoculation of Rhizobium+Pseudomonas recorded markedly higher nodule occupancy than Rhizobium alone at different root portions with both seed and soil inoculation methods.